ANALISIS PENGARUH KEADILAN ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN MEDIASI KOMITMEN ORGANISASI DI KANTOR BADAN PERTANAHAN NASIOANAL (BPN) KOTA BANJARMASIN - Syafriyanti Syafriyanti; Hastin Umi Anisah (Universitas Lambung Mangkurat, 2021)
This study was conducted to analyze the effect of organizational justice and job satisfaction on the Organizational Citizenship Behavior (OCB) of contract employees at the National Land Agency Banjarmasin with Organizational commitment as mediation. The basis for this research is, because of the large amount of work carried out by the organization, employees are required to work more in completing each task that has been assigned to them, employees also often work beyond the predetermined working time, so that the opportunity to help colleagues who have been assigned to them others are very thin, unless the boss asks. The research sample consisted of 33 people who were all contract employees/PPNPN from the research object. Data collection was carried out through a questionnaire in order to provide an assessment of the application of justice in the organization (X1), test how satisfied employees are at work (X2), employee commitment to the organization (Z) and measure how much OCB of employees in the organization. The data analysis method used is Partial Least Square (PLS) 3. The results showed that, organizational justice has a positive and significant effect on Organizational Citizenship Behavior (OCB), but not with job satisfaction which has no significant effect on Organizational Citizenship Behavior (OCB). As for organizational justice has a positive and significant influence on organizational commitment, as well as organizational commitment which has a positive and significant influence on Organizational Citizenship Behavior (OCB), as well as organizational justice has a positive and significant effect on employee Citizenship Behavior (OCB), both directly and through mediation of Organizational Commitment.